Trigona Honey For Infection Control And Wound Healing In Diabetic Foot Ulcers: A Case Report - Sukarni Sukarni; Djoko Priyono; Kharisma Pratama (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Diabetes-related foot ulcer (DFU) is a chronic complication of diabetes mellitus that is frequently accompanied by infection and carries a high risk of lower-limb amputation. Effective infection control and continuous monitoring of wound progression are critical determinants of therapeutic success. Trigona honey has been reported to possess antibacterial and anti-inflammatory properties that may support wound healing. Case Presentation: A 47-year-old man with a five-year history of type 2 diabetes mellitus presented with a Wagner grade 2 DFU on the left toe following trauma. The ulcer exhibited signs of severe infection, including erythema, pain, and purulent exudate. Laboratory findings revealed leukocytosis and elevated blood glucose levels. The patient received systemic antibiotic therapy in combination with standard wound care, including cleansing, debridement, and topical application of Trigona honey using gauze dressings. Dressings were changed every 24–96 hours depending on wound condition. Results: Over a 30-day treatment period, there was a gradual reduction in infection status and progressive improvement in wound healing, characterized by decreased inflammation and the formation of healthier granulation tissue. However, prolonged use of Trigona honey during the proliferative phase was associated with maceration and hypergranulation around the wound. Conclusion: Trigona honey, when used as an adjuvant therapy, is effective in controlling infection and promoting wound healing during the early phase of DFU. Continued application should be reassessed if signs of maceration or hypergranulation occur, and treatment strategies should be adjusted according to the wound-healing phase to optimize clinical outcomes.